SARS-CoV-2 infection of the central nervous system in a 14-month-old child: A case report of a complete autopsy - Ismael Gomes; Karina Karmirian; Júlia T. Oliveira; Carolina da S.G. Pedrosa; Mayara Abud Mendes; Fernando Colonna Rosman; Leila Chimelli; Stevens Rehen (Elsevier, 2021)
Background: Neurological and other systemic complications occur in adults with severe COVID-19. Here we describe SARS-CoV-2 infection complicated by neuroinvasion in the post-mortem tissues of a child. Methods: We performed a complete autopsy of a 14-month-old child who died of COVID-19 pneumonitis. Histological sections of multiple organs were stained with haematoxylin and eosin. Luxol fast blue staining for myelin and immunohistochemistry were performed in selected areas of the brain. The presence of SARS-CoV-2 was investigated by immunostaining with anti-spike protein antibody and by RT-qPCR. Findings: Lesions included microthrombosis, pulmonary congestion, interstitial oedema, lymphocytic infiltrates, bronchiolar injury, collapsed alveolar spaces, cortical atrophy, and severe neuronal loss. SARS-CoV-2 staining was observed along the apical region of the choroid plexus (ChP) epithelium and in ependymal cells of the lateral ventricle, but was restricted to ChP capillaries and vessels in some regions. SARS-CoV-2 infection of brain tissue was confirmed by RT-qPCR in fragments of the ChP, lateral ventricle, and cortex. Interpretation: Our results show multisystemic histopathological alterations caused by SARS-CoV-2 infection and contribute to knowledge regarding the course of fatal COVID-19 in children. Furthermore, our findings of ChP infection and viral neurotropism suggest that SARS-CoV-2 may invade the central nervous system by blood-cerebrospinal fluid barrier disruption. Funding: Carlos Chagas Filho Foundation for Supporting Research in the State of Rio de Janeiro (FAPERJ); the National Council for Scientific and Technological Development (CNPq) and Coordination for the Improvement of Higher Education Personnel (CAPES), in addition to intramural grants from D'Or Institute for Research and Education. Editor's Note: This translation in Portuguese was submitted by the authors and we reproduce it as supplied. It has not been peer reviewed. Our editorial processes have only been applied to the original abstract in English, which should serve as reference for this manuscript. Resumo: Complicações sistêmicas e neurológicas foram descritas em adultos com COVID-19 grave. Neste trabalho, descrevemos a infecção por SARS-CoV-2, incluindo sua neuroinvasão, nos tecidos post-mortem de uma criança. Métodos: Realizamos a autópsia completa de uma criança de 14 meses que morreu de pneumonite por COVID-19. Cortes histológicos de múltiplos órgãos foram corados com Hematoxilina e Eosina. A coloração de Luxol Fast Blue para mielina e imuno-histoquímica foram realizadas em áreas selecionadas do cérebro. A presença de SARS-CoV-2 foi investigada por imunomarcação com anticorpo anti-proteína spike e por RT-qPCR. Achados: As lesões incluíram microtrombose, congestão pulmonar, edema intersticial, infiltrados linfocíticos, lesão bronquiolar, colapso dos espaços alveolares, atrofia cortical e perda neuronal grave. A presença de SARS-CoV-2 foi observada ao longo da região apical do epitélio do plexo coróide (PC) e nas células ependimárias do ventrículo lateral, mas ficou restrita aos capilares e vasos do PC em outras regiões. A infecção do tecido cerebral por SARS-CoV-2 foi confirmada por RT-qPCR em fragmentos do PC, ventrículo lateral e cortex cerebral. Interpretação: Nossos resultados mostram alterações histopatológicas multissistêmicas causadas pela infecção por SARS-CoV-2 e contribuem para ampliar o conhecimento sobre a evolução da COVID-19 fatal em crianças. Além disso, nossos achados sobre a infecção no PC e neurotropismo viral sugerem que o SARS-CoV-2 pode invadir o sistema nervoso central pela ruptura da barreira sangue-líquido cefalorraquidiano. Financiamento: Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro (FAPERJ); Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPQ) e Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), além de financiamento intramural do Instituto D'Or de Pesquisa e Educação.